Impacts of locally managed periodic octopus fishery closures in Comoros and Madagascar: short-term benefits amidst long-term decline - McCabe, Mary K.; Mudge, Laura; Randrianjafimanana, Tahiry; Rasolofoarivony, Nestin; Vessaz, Fanny; Rakotonirainy, Robertin; Said, Faissoil Ahmed; Rakotoarisoa, François; Ratoniherison, Tsiorisoa; Box, Steve; Cox, Courtney (Frontiers in Marine Science, 2024)
Octopus fisheries face heightened demand driven by depleted fish stocks and escalating economic value, leading to overextraction of octopus populations and magnifying threats to coastal ecosystems and the livelihoods of fishers who depend on them. Implementation of management strategies such as periodic fishing closures can offer sanctuary for octopus, providing the necessary space and time for the growth and reproduction of this rapidly proliferating species. Despite evidence of positive management outcomes, the role of periodic closures in the long-term sustainability of octopus populations remains uncertain. Here, we examine trends in octopus landings over time and the effects of periodic closures along the Mozambique Channel from Comoros to Madagascar (12°-25°S). Long-term trends in octopus landings varied across three regions: generally stable over a 6-year period in Comoros, increasing over a 4-year period in the Barren Isles and declining over a 17-year period in Atsimo Andrefana, Madagascar. We observed a significant increase in mean catch per unit effort (CPUE, kilograms/fisher-day), and mean total catch (kilograms/day) following periodic closures across villages extracting octopus from closure areas. When evaluating each region independently, we observed this positive effect across Comoros and Atsimo Andrefana, Madagascar while trends in the Barren Isles showed no effect of octopus closures. We applied generalized linear mixed models to examine the influence of 10 covariates on mean daily total catch and CPUE within 7 days and 30 days post-closure. Baseline conditions (quantified by the pre-closure CPUE and daily total catch), closure duration and start month of closure had positive, statistically significant correlations with post-closure CPUE and daily total catch. Additionally, closure duration from 13 to 16 weeks and closure size of approximately 70 hectares were qualitatively associated with net gains in CPUE. Although periodic closures yield positive outcomes for octopus fisheries, the effects may be short-lived, as observed in Atsimo Andrefana, Madagascar, where catch declined over the long-term despite temporary improvements. Our findings underscore a need for a diverse portfolio of management strategies to restore and sustain populations over the long-term.